Obesity and Its Associated Cancer-Related Risk with Gynaecology - Alsannan, Baydaa; Upadhyay, Amit; V. Raman , Vinay; Bajarang Singh, Jay; Raj , Amar; Haridas, Kiran (Journal of Coastal Life Medicine, 2023)
Obesity is becoming a life-threatening problem leading to gynaecological malignancies. Emerging data indicate that obesity plays a part in the emergence of gynaecological cancers. The study’s goal is to look into the likelihood of gynaecological cancers according to obesity using a cohort study of 400 female patients from a hospital in Chennai, India. Altogether, 200 patients were obese, while the rest 200 were of normal weight. The study indicates that obesity leads to a higher risk of endometrial cancer, intermediate risk of breast and ovarian cancer and relatively negligible risk of ovarian cancer when compared to the normal weight cancer patients.